Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
2, 6, 11
Step-by-step explanation:
To evaluate f(- 1) substitute x = - 1 into f(x)
f(- 1) = 2(- 1)³ - 3(- 1)² + 7 = 2(- 1) - 3(1) + 7 = - 2 - 3 + 7 = 2
Similarly
f(1) = 2(1)³ - 3(1)² + 7 = 2(1) - 3(1) + 7 = 2 - 3 + 7 = 6
f(2) = 2(2)³ - 3(2)² + 7 = 2(8) - 3(4) + 7 = 16 - 12 + 7 = 11
Answer:
f(-1) = 2
f(1) = 6
f(2) = 11
Step-by-step explanation:
Got it right on Edge (⌣_⌣”)
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.